The Transformation of Egypt. - Cooper, Mark N. (Routledge Library Editions: Egypt., 2012)
The assassination of Sadat brings to an end another era in Egyptian history. This book examines the crucial issues in the transformation of Egypt in the period between the death of Nasser and the murder of Sadat. Focusing on the upheavals in the Egyptian political and economic structure over the last twenty years, the book explains the change in Egypt's international orientation through a careful examination of domestic factors. The switch from Nasser's state socialist-political economy to Sadat's more laissez-faire approach and the institutional and structural links bet.